Different Ferroxidases Activities in Sera and Saliva of Iraqi Patients with β-thalassemia Major - Muhtada Ali (Journal of Global Pharma Technology, 2018)
Background and aim: β-thalassemia is the most common recessive hemoglobin disease, caused by defective in normal hemoglobin β-globin chain production. It results in large number of red blood cells being destroyed, which leads to anemia. We conducted this study to investigate the different ferroxidases activities in sera and saliva samples of these patients. Materials and methods: Serum and saliva specimens were collected from 91 males, 51 of them were β-thalassemia major patients, aged 11 to 26 years (mean= 15.28 ± 4.45 years) and 40 of them were age and gender-matched healthy controls. Results: The obtained results were as follows: in sera samples the activity and the specific activity of: total ferroxidase, and non-ceruloplasmin ferroxidase, were highly significantly decreased (P<0.001), with a significant increase in the activity and specific activity of ceruloplasmin ferroxidase (p<0.05) were found in the patients compared with the control. Meantime the results in saliva of the patients group, showed a none-significant increase (p>0.05) in the activity of non-ceruloplasmin ferroxidase and the specific activity of total ferroxidase in comparison with that of the control group, this was accompanied with none significant increase in ceruloplasmin activity and specific activity (p>0.05). Conclusion: According to our results, it can be suggested that the reduction in ferroxidase activities other than ceruloplasmin ones contributes in the oxidative stress that was measured previously in β-thalassemia patients. Furthermore, saliva cannot be served as an alternative diagnostic fluid for this disease instead of serum as far as the present study measured parameters are concerned.Key words: Ferroxidase, Thalassemia, Deferasirox, Ceruloplasmin.